2021
DOI: 10.1111/ijpo.12879
|View full text |Cite
|
Sign up to set email alerts
|

Use of person‐centred language among scientific research focused on childhood obesity

Abstract: Background: Stigma towards children with obesity can begin as early as 3 years old, leading to increased risk for poorer mental health outcomes and lower quality of life. This includes discriminatory language used by peers and adults, which may be compounded by use within the medical community and in published research.Objectives: Our primary objective was to investigate adherence to person-centred language (PCL) in childhood obesity-related medical publications.Methods: We searched PubMed for childhood obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…As Ottwell et al state, and as we would like to reiterate, ‘non-PCL is most likely not malicious and is often a result of adherence to an unchanged status quo’ 18. While the use of non-PCL has been investigated in publications regarding topics such as AUD,17 dermatology18 and childhood obesity,29 it has yet to be examined among HIV research. Our study of the use of non-PCL within HIV publications serves to fill this gap and increase awareness, a key component of translation of research into the medical community30 and clinical practice 31.…”
Section: Discussionmentioning
confidence: 92%
“…As Ottwell et al state, and as we would like to reiterate, ‘non-PCL is most likely not malicious and is often a result of adherence to an unchanged status quo’ 18. While the use of non-PCL has been investigated in publications regarding topics such as AUD,17 dermatology18 and childhood obesity,29 it has yet to be examined among HIV research. Our study of the use of non-PCL within HIV publications serves to fill this gap and increase awareness, a key component of translation of research into the medical community30 and clinical practice 31.…”
Section: Discussionmentioning
confidence: 92%
“…Representing an enormous global challenge of increasing proportion, obesity in general, and childhood obesity in particular, which may predate adult obesity, and which is on the rise, may predictably and progressively induce multiple adverse health impacts, including depression and poor mental health, even among very young children 34,35 and especially if it persists unabated into adolescence. 36,37 As well, even though mental health attributes of childhood obesity have been discussed for some time, the failure to detect or resolve mental health problems or mitigate these early on may be expected to have marked adverse life long effects. Moreover, even if therapy prevails, this can be impeded in the presence of undetected or untreated parental depression that may not be a treatment focus.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…However, despite multiple calls to academic institutions, public health‐authorities, professional organizations including healthcare, media, public health services and governing bodies, to adopt a public narrative about childhood obesity that reflects the current scientific knowledge of the disease, progress remains slow. Indeed, a recently published study found very low adherence to patient‐centred language in childhood obesity‐related academic research published between 2018 and 2020 and available on PubMed, with a majority of the articles including stigmatizing non‐patient‐centred labels 26 . However, among pediatric obesity articles indexed in PubMed over the last 20 years, we see a sharp decline in the use of non‐patient‐centred language in the titles of peer‐reviewed papers from 2014 onward (Figure 1).…”
Section: Figurementioning
confidence: 99%
“…Indeed, a recently published study found very low adherence to patient-centred language in childhood obesity-related academic research published between 2018 and 2020 and available on PubMed, with a majority of the articles including stigmatizing non-patient-centred labels. 26 However, among pediatric obesity articles indexed in PubMed over the last 20 years, we see a sharp decline in the use of non-patient-centred language in the titles of peer-reviewed papers from 2014 onward (Figure 1). Interestingly, 2019 represents the first time that a higher number of publications used people-first language in their titles than those that did not.…”
mentioning
confidence: 99%